Menyembunyikan Nasab Anak - Pratiwi, Nila; Muhammad, Nasrizal (Jurnal AL-AHKAM, 2024)
The cause of nasab relationship is marriage. The child is related to the mother through pregnancy, and the child is related to the father through marriage. The marriage relationship that causes the nasab relationship is a valid marriage, invalid marriage, and wathi' syubhah. If the pregnancy occurs outside of a valid marriage, or the marriage is invalid, then the child does not have a nasab relationship with the father even though it is determined by various methods in determining nasab, such as recognition, proof, lottery, tracking / tracing, claims / demands, judge decisions, and others. Thus, no rights are obtained in the absence of a nasab relationship. There is no right to inherit from each other, no right to guardianship in marriage, etc. In fact, the father has the right to marry the daughter because she is not included in the women who are forbidden to marry. This article is a normative research in which the author uses the type of library research with secondary data sources, in the form of documentation and other literature materials related to the material discussed.